Germinal centre lymphomas: advances in diagnostic and therapeutic intervention - Korfi, Koorosh; Fitzgibbon, Jude (Henry Stewart Talks, 2017)
Technological advances in precision medicine, Follicular lymphoma and its genetic landscape, Advances in patient stratification at diagnosis, Novel therapeutic strategies, Clonal evolution and heterogeneity